The Concept of Dinar and Dirham Currency in Perspective Ibrahim Umar Vadillo - Fairuz Azzahra Irsyad; Muhammad Arif (PT. Islamic Research Publisher, 2024)
Since the early Islamic era, gold and silver, known as dinars and dirhams, have been used as a means of transactions in international trade. The application of the dinar and dirham actually functions as a strategy to deal with the dominance of the US dollar and euro, with the aim of reducing dependence on Islamic countries, including Indonesia. This concept also has the potential to be applied in efforts to limit usury practices, speculation and uncertainty. In this article, the author applies literature study research methods to outline various crucial aspects related to efforts to introduce dinars and dirhams as legal means of payment in Indonesia. Nazir explained that literature study is a data collection technique that involves reviewing books, literature, notes and reports that are relevant to the issue being discussed.